Pembangunan kembali Istano Basa Pagaruyung dan Proses Pengelolaannya Setelah Kebakaran (2007-2021) - Anisa Anisa; Najmi Najmi (Jurnal Kronologi, 2023)
This study discusses the Rebuilding of Istano Basa Pagaruyung and its Management Process After Burning (2007-2021). The purpose of this study is to find out how the government's efforts in managing Istano Basa Pagaruyung after the fire started from rebuilding and tourism potential owned by Istano Basa Pagaruyung, namely the attraction of Istano Basa Pagaruyung, Istano Basa Pagaruyung facilities, access to Istano Basa Pagaruyun. This study uses the historical method through four stages of research, namely heuristics, source criticism, interpretation, and historiography. From the discussion, it can be seen that, (1) Efforts made by the government in rebuilding Istano Basa Pagaruyung include the formation of a committee, collecting funds from individual/institutional donations, donations of demand deposits, insurance funds, donations from Regents/Mayors throughout West Sumatra. , and grant assistance from the West Sumatra Regional Government, (2) the management carried out by DISPASPORA from 2007-2021 are: (1) Facilities (Amenities) of Istano Basa Pagaruyung, (2) Access (Accessibility) of Istano Basa Pagaruyung, (3) Hospitality (Ancellery), (4) performances (Attractions).